2021
DOI: 10.1017/dmp.2021.271
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Prevalence of Disaster-Related Deep Vein Thrombosis in Minamiaso Village After the 2016 Kumamoto Earthquakes: A Prospective Cross-Sectional Analysis

Abstract: Objective: This study aimed to examine the prevalence of deep vein thrombosis (DVT) among evacuees in Minamiaso, a village which was temporarily isolated after the earthquakes, from the acute to recovery phase after the 2016 Kumamoto Earthquakes (GLIDE no: EQ-2016-000033-JPN). Methods: This prospective study, which was approved by Fukui University Medical Research Ethics Committee (approval no. 20160024 and 20160089), enrolled 181 evacuees (73.9 ± 11.6 y) who participated in a series of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Both the patients were subsequently diagnosed with Pulmonary embolism triggered by FCMVTs presenting the “Blowfish sign.” Although the fresh thrombi disappeared after anticoagulant therapy, few calcified thrombi remained. FCMVT has been commonly detected among residents of disaster zones using lower leg vein ultrasonography 1 . We termed the characteristic ultrasound image of FCMVTs that had a mixture of low‐brightness echoic thrombi and calcified thrombi as the “Blowfish sign.” 2 However, no studies have reported an association between FCMVTs showing the “Blowfish sign” and the development of acute pulmonary embolism has been reported.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Both the patients were subsequently diagnosed with Pulmonary embolism triggered by FCMVTs presenting the “Blowfish sign.” Although the fresh thrombi disappeared after anticoagulant therapy, few calcified thrombi remained. FCMVT has been commonly detected among residents of disaster zones using lower leg vein ultrasonography 1 . We termed the characteristic ultrasound image of FCMVTs that had a mixture of low‐brightness echoic thrombi and calcified thrombi as the “Blowfish sign.” 2 However, no studies have reported an association between FCMVTs showing the “Blowfish sign” and the development of acute pulmonary embolism has been reported.…”
Section: Figurementioning
confidence: 99%
“…FCMVT has been commonly detected among residents of disaster zones using lower leg vein ultrasonography. 1 We termed the characteristic ultrasound image of FCMVTs that had a mixture of low-brightness echoic thrombi and calcified thrombi as the "Blowfish sign." 2 However, no studies have reported an association between FCMVTs showing the "Blowfish sign" and the development of acute pulmonary embolism has been reported.…”
mentioning
confidence: 99%